P.177 Assessing lesion severity in a mouse model of intracerebral hemorrhage. (June 2022) - Pendleton, N; Sylvian, N; Hou, H; Pushie, J; Kelly, M; Peeling, L
Abstract : Background: Intracerebral hemorrhage (ICH) is caused by the rupture of a blood vessel, resulting in bleeding into the brain. This type of stroke accounts for 12-15% of all strokes and is the most fatal type of stroke (40% mortality rate). ICH stroke presents a greater burden to survivors as 90% of ICH survivors have some degree of disability. Because of the poor patient outcomes, there is a clear need for identifying new treatments as well as establishing the efficacy of existing treatments. Methods: Using previously described techniques we aim to establish a mouse model of ICH at the University of Saskatchewan. We observed them at a 1- 24-, 48- and 72hr mark post-stroke and scored for neurological deficits. Results: We currently have conducted 23 model trials. We have data on mice at 1-, 24, and 72 hr post-stroke. We have observed and begun to analyze a lesion area that can be seen in H&E stained sections, and further assessed with FTIR, and synchrotron modalities. Conclusions: We have analyzed several of the specimens with FTIR imaging and synchrotron analysis with the Canadian Light Source. We have preliminary results of the progression of metabolites in the hematoma and peri-hematoma zone of the ICH.